The American - Booth, Martin (Picador, 2010)
The locals in the southern Italian town where he lives call him Signor Farfalla--Mr. Butterfly: for he is a discreet gentleman who paints rare butterflies. His life is inconspicuous--mornings spent brushing at a canvas, afternoons idling in the cafes, and evening talks with his friend the town priest over a glass of brandy. Yet there are other sides to this gentleman's life: Clara: the young student who moonlights in the town bordello. And another woman who arrives with $100,000 and a commission, but not for a painting of butterflies. With this assignment returns the dark fear that has dogged Signor Farfalla's mysterious life. Almost instantly, he senses a deadly circle closing in on him, one which he may or may not elude. Part thriller, part character study, part drama of deceit and self-betrayal, A Very Private Gentleman shows Martin Booth at the very height of his powers.